The danger of premature interment - Taylor, Joseph, 1762?-1844 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Danger of Premature Interment" by Joseph Taylor is a medical treatise written in the early 19th century. The work addresses the alarming phenomenon of premature burial, presenting numerous historical anecdotes and cases where individuals were mistakenly declared dead but later revived. The author aims to raise awareness about the importance of proper examination before interment to prevent such grave mistakes. The opening of the book sets a grim tone as Taylor reflects on the horror of being buried alive, emphasizing the necessity of caution in determining death. He shares poignant accounts from history, illustrating instances when individuals were misjudged as dead and later revived, highlighting the precariousness of life and the responsibility of the living to ensure the deceased are not hastily interred. His argument is supported by a blend of medical advice and cultural practices surrounding death and burial, laying a foundation for the discussions that follow throughout the volume. (This is an automatically generated summary.)
Release date is 2023-10-31
Aaron Adrignola, Gísli Valgeirsson and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Funeral rites and ceremonies; Burial, Premature